2019
DOI: 10.1002/pssa.201800861
|View full text |Cite
|
Sign up to set email alerts
|

Growth of CuSbS2 Single Crystal as an Environmentally Friendly Thermoelectric Material

Abstract: High‐quality p‐type chalcostibite CuSbS2 single crystal is successfully synthesized by zone melting method for investigating fundamental properties. The grown crystal is orthorhombic structure and nearly stoichiometric with slightly Cu‐rich composition. The electrical properties are the hole concentration of 8.0 × 1016 cm−3, conductivity of 0.8 S cm−1, and mobility of 65 cm2 V−1 s−1 by Hall effect measurement at room temperature. Intrinsic low thermal conductivity in CuSbS2 single crystal is 0.9 W mK−1 at room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Furthermore, Raman spectroscopy was performed to confirm the structural characterization and phase identification of intermetallic compounds. The Cu 2 Sb single-crystal nanoparticle exhibited several distinct peaks at 133.91, 184.42, and 243.35 cm –1 , which are shown in the Raman spectrum in Figure B. The peaks corresponding to 133.91 and 184.42 cm –1 exhibited due to the rocking and stretching vibration of compounds Cu–Sb and Sb–Sb. Similarly, the 243.35 cm –1 peaks belong to the E 2g band, in consistence with previously reported Cu 2 Sb bands.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Raman spectroscopy was performed to confirm the structural characterization and phase identification of intermetallic compounds. The Cu 2 Sb single-crystal nanoparticle exhibited several distinct peaks at 133.91, 184.42, and 243.35 cm –1 , which are shown in the Raman spectrum in Figure B. The peaks corresponding to 133.91 and 184.42 cm –1 exhibited due to the rocking and stretching vibration of compounds Cu–Sb and Sb–Sb. Similarly, the 243.35 cm –1 peaks belong to the E 2g band, in consistence with previously reported Cu 2 Sb bands.…”
Section: Resultsmentioning
confidence: 99%
“…CuSbS 2 single crystals were grown from its feed polycrystalline by the zone melting method at a growth temperature of 600°C, the temperature gradient of 40°C/cm, and growth speed of 4 mm/day as previously reported. 15) The grown crystals were cut with a diamond blade, polished mechanically with a 0.01 µm Al 2 O 3 paste, and then etched with a 5% Br 2 / Methanol solution for 5 min. TE measurements were carried out along the c-axis because the sample size in other directions was too small for measurements.…”
Section: Methodsmentioning
confidence: 99%
“…We focused on a chalcostibite CuSbS 2 single crystal as an environmentally friendly TE material because of its stable orthorhombic structure until reaching the melting point, as well its characteristically low thermal conductivity <1.0 W/mK. 15) We have reported that the CuSbS 2 single crystals were grown using the zone-melting method at 600°C, and its TE properties were measured at room temperature. Without a grain-boundary barrier, single crystal samples exhibit potential for better electrical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Derivatives of PbTe and Bi 2 Te 3 have demonstrated high efficiency as thermoelectrics and have seen commercial adoption, , but the low elemental abundance, cost, and toxicity of these products continue to limit their widespread use . The copper–antimony–sulfide (CAS) subset of materials is composed of low-cost, earth-abundant compounds with properties rendering them suitable for photovoltaic and thermoelectric applications. The CAS system features four main compounds: tetrahedrite (Cu 12 Sb 4 S 13 ), chalcostibite (CuSbS 2 ), skinnerite (Cu 3 SbS 3 ), and famatinite (Cu 3 SbS 4 ) . Famatinite features key properties that have a potential to benefit applications in solar cells and thermoelectric devices.…”
Section: Introductionmentioning
confidence: 99%